2005
DOI: 10.1177/0363546504267349
|View full text |Cite
|
Sign up to set email alerts
|

American Collegiate Men's Ice Hockey

Abstract: The risk of injury in men's collegiate ice hockey is much greater during games than during practices. Concussions are a main cause for time lost and remain an area of major concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
241
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(260 citation statements)
references
References 20 publications
(17 reference statements)
10
241
2
5
Order By: Relevance
“…The most common denominators for incidence calculation are player hours, athlete exposures, and games played. [1][2][3][8][9][10]16,17,24,25,29 Flick 10 reported an incidence rate of 3.1 per 1000 athlete exposures for Division 1 university ice-hockey players in 1 season. Wennberg and Tator 29 reported an incidence of concussion in the National Hockey League that ranged from 1.81 per 1000 athlete exposures in 1998-1999 to a low of 1.04 per 1000 athlete exposures in 2005-2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common denominators for incidence calculation are player hours, athlete exposures, and games played. [1][2][3][8][9][10]16,17,24,25,29 Flick 10 reported an incidence rate of 3.1 per 1000 athlete exposures for Division 1 university ice-hockey players in 1 season. Wennberg and Tator 29 reported an incidence of concussion in the National Hockey League that ranged from 1.81 per 1000 athlete exposures in 1998-1999 to a low of 1.04 per 1000 athlete exposures in 2005-2006.…”
Section: Discussionmentioning
confidence: 99%
“…Previous sport concussion studies demonstrated that concussion predominantly occurs in game situations. [1][2][3]10,30 Gerberich et al, 11 a commonly cited retrospective study on recurrent concussions, states that the relative risk of concussions is 4 times higher than for individuals without this history. A prospective survey study of US high school and college football athletic trainers by Guskiewicz et al 15 found that players who had sustained 1 concussion were 3 times more likely to sustain a second concussion than those players who had not sustained a previous injury.…”
Section: Discussionmentioning
confidence: 99%
“…AC joint injuries are one of the most common problems in the athletic population [7]. They account for 3% of all shoulder injuries and 40% of sports-related shoulder injuries [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, even with the use of protective headgear the incidence of mild traumatic brain injury (mTBI) known as concussions have not, and continue to be a concern in both recreational and professional sports [2][3][4][5]. A recent survey reported 110 in 100,000…”
Section: Introductionmentioning
confidence: 99%